Prediction of interfacial area concentration in a small diameter round pipe. (March 2019) - Wang, Guanyi; Zhu, Qingzi; Dang, Zhuoran; Yang, Xiaohong; Ishii, Mamoru
Highlights: Two-group IATE are evaluated using the small pipe data for the first time. Recent progress on two-group IATE modeling are summarized and evaluated. New models for bubble coalescence using log-normal size distribution are developed. Abstract: Accurate prediction of interfacial area concentration (IAC) is of great importance in the two-fluid model. As a promising IAC prediction method, the interfacial area transport equation (IATE) was developed to dynamically predict the IAC and to eliminate the shortcomings of the flow regime-based IAC correlations, which is currently used in most thermal–hydraulic system codes. To extend the applicability of the IATE from bubbly flow to slug and churn-turbulent flow, the two-group IATE was developed by representing the IAC of sphere/distorted bubbles and cap/slug bubbles separately. Several studies have been performed in the past focusing on the constitutive modeling and experimental benchmark. However, few data are collected in small size pipes ( D H ⩽ 2 D c ), hence the applicability of the current two-group IATE models on small size pipes has not been well evaluated. In this study, a comprehensive database including bubbly, slug, churn-turbulent flow is established in a round pipe with a diameter of 25.4 mm ( DH ≈ 2 Dc ), and the applicability of two-group IATE models for round pipe has been checked against the data. The measured IAC can be predicted by the two-group IATE with the constitutive models developed for moderate size pipe with errors less than 25% except at the bubbly to slug transition flow conditions. At the transition flow, drastic intergroup void fraction and IAC transport are observed along the flow direction. The model cannot predict this intergroup transfer and overestimates the IAC. Recent improvements on the original models focusing on the one-group to two-group transition flow in a moderate size pipe are also evaluated and the results are still not satisfying. The reasons for this discrepancy are analyzed in detail and improvements including re-deriving the coalescence terms using more accurate log-normal bubble size distribution and experimental coefficients optimizing have been performed. Using the newly derived models with optimized coefficients, the two-group IATE can predict the IAC axial development for all flow conditions with an error less than 25%. The averaged prediction error for the bubbly to slug transition flow conditions decreases from 47.19% to 8.03%.